Evaluation of bioenergetic and mitochondrial function in liver transplantation - Martins, Rui Miguel (Clin Mol Hepatol, 2019)
BACKGROUND/AIMS: We measured changes in mitochondrial function and bioenergetics that occur during ischemia/ reperfusion in fresh liver samples of patients undergoing liver transplantation. These variations correlated with markers of liver function and clinical outcome. Ischemia/reperfusion injury related to liver transplantation affects mitochondrial function and bioenergetics. Experimental studies were conducted to identify the role of bioenergetics and mitochondrial dysfunction. To the best of our knowledge, no investigation of these two factors’ impacts on liver transplantation has been performed. METHODS: This was a prospective study of 28 patients who underwent liver transplantation. We measured parameters of mitochondrial function and bioenergetics in biopsies performed during the procedure. RESULTS: We observed a statistically significant reduction in mitochondrial membrane potential, an increase in lag phase, and decreases in mitochondrial respiration and adenosine triphosphate content (P<0.010). Higher postoperative aminotransferase peaks correlated with worse mitochondrial function; mitochondrial respiration correlated with arterial lactate (P<0.010). CONCLUSIONS: There is a relationship between mitochondrial function and ischemia/reperfusion injury. The future use of these clinical markers as prognostic factors may allow early identification of post-transplant liver failure and may indicate the need to perform a new transplant.